The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1096/fj.202201518r
|View full text |Cite
|
Sign up to set email alerts
|

Innately expressed estrogen‐related receptors in the skeletal muscle are indispensable for exercise fitness

Abstract: Transcriptional determinants in the skeletal muscle that govern exercise capacity, while poorly defined, could provide molecular insights into how exercise improves fitness. Here, we have elucidated the role of nuclear receptors, estrogen-related receptor alpha and gamma (ERRα/γ) in regulating myofibrillar composition, contractility, and exercise capacity in skeletal muscle. We used muscle-specific single or double (DKO) ERRα/γ knockout mice to investigate the effect of ERRα/γ deletion on muscle and exercise p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
(153 reference statements)
2
9
0
Order By: Relevance
“…Exercise trained mice with HLI experienced smaller declines in muscle power output (Figure 3K) and performed ∼45% more total work (Figure 3L) than the control mice with HLI which carried a large effect size (17 2 = 0.16). These findings are consistent with the multitude of positive effectors of exercise training in the skeletal muscle and vasculature (93, 98, 102–108). It should be noted that exercise training and the control group were all from the C57BL6/J genetic strain of mice and thus have a rapid recovery from HLI.…”
Section: Discussionsupporting
confidence: 85%
“…Exercise trained mice with HLI experienced smaller declines in muscle power output (Figure 3K) and performed ∼45% more total work (Figure 3L) than the control mice with HLI which carried a large effect size (17 2 = 0.16). These findings are consistent with the multitude of positive effectors of exercise training in the skeletal muscle and vasculature (93, 98, 102–108). It should be noted that exercise training and the control group were all from the C57BL6/J genetic strain of mice and thus have a rapid recovery from HLI.…”
Section: Discussionsupporting
confidence: 85%
“…Pathways that were significantly SLU-PP-332 upregulated in both muscle types are shown in Figure D,E. Interestingly, these pathways are quite distinct from those identified as downregulated in the skeletal muscle ERRα/γ double KO mice, where oxidative phosphorylation, TCA cycle, and mitochondrial function genes were well represented . However, we previously showed that SLU-PP-332 induced a similar set of energetic genes/pathways in cardiomyocytes as were downregulated in the skeletal muscle double ERRα/γ KO consistent with SLU-PP-332 activation of ERRs.…”
Section: Resultssupporting
confidence: 60%
“…The ERRs play important roles in the regulation of energy metabolism and fuel selection. Loss of ERRα or ERRγ function leads to reduced muscle oxidative function and reduced functional endurance; ,, thus, pharmacological activation of these receptors may lead to beneficial metabolic effects associated with increased skeletal muscle activity for the treatment of metabolic diseases. In this study, we characterize the ability of a pan ERRα/β/γ synthetic agonist with ∼4-fold ERRα selectivity over ERRγ (SLU-PP-332) to function as an exercise mimetic and improve muscle and metabolic function both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…59 Subcluster 5 was also found to be enriched with ESRRG expression (Figure S4C and S4D), which has been shown to enhance ischemic angiogenesis and oxidative function of muscle in murine PAD models. 60,61 Coincidentally, PAD type II myonuclei also displayed substantial upregulation of PFKFB3 (Figure S4D), a known stimulator of glycolysis which is also linked to ischemic myopathy. 62 Unsupervised clustering of 5494 hybrid I-II myonuclei generated seven distinct populations (Figure S6A).…”
Section: Patients With Pad Display Unique Myonuclei Populations and T...mentioning
confidence: 95%